Strategies Of Teaching Teachers In Increasing Interest In Learning The Qur'an At TPQ Syahidul Ikhlas - Puspasari, Hikmah; Arif, Mahmud; Puspitasari, Dea (Yayasan Rahmat Islamiyah, 2025)
The low interest of students in learning the Qur'an at TPQ Syahidul Ikhlas is the main focus of this study. The study aims to identify teaching strategies applied by teachers to increase interest in learning the Qur'an among students. The approach used is qualitative with a case study method, through observation, interviews,and documentation to obtain in-depth data. The results of the study indicate that the application of the murojaah method routinely, repeatedly, and a personal approach adjusted to the abilities of students is effective in increasing students' interest in learning, understanding, and memorization of the Qur'an. The importance of innovation and variation in learning methods is proposed so that the process of learning to recite the Qur'an becomes more enjoyable and is able to foster a love and deeper understanding of the contents of the Qur'an. With this strategy, students are expected to be able to achieve optimal results in learning the Qur'an.